Impact of SDH Mutations in Alternaria solani on Recently Developed SDHI Fungicides Adepidyn and Solatenol - Budde-Rodriguez, Sarah (Plant disease, 2021)
Early blight, caused by Alternaria solani, is observed annually in all midwestern potato production areas. The use of foliar fungicides remains a primary management strategy. However, A. solani has developed reduced sensitivity or resistance to many single-site fungicides such as quinone outside inhibitor (QoI, FRAC group 11), succinate dehydrogenase inhibitor (SDHI, FRAC group 7), demethylation inhibitor (DMI, FRAC group 3), and anilinopyrimidine (AP, FRAC group 9) fungicides. Boscalid, fluopyram, solatenol, and adepidyn are EPA-registered SDHI fungicides used commercially on a variety of crops, including potato. Five SDH mutations have been characterized previously in A. solani that affect the efficacy of boscalid while only one of these mutations has been demonstrated to negatively affect fluopyram efficacy. Conidial germination assays were used to determine if a shift in sensitivity has occurred in these SDHI fungicides. A. solani isolates collected prior to the commercial application of SDHI fungicides (baseline) were compared with recently collected isolates (nonbaseline). Greenhouse evaluations were conducted also to evaluate the efficacy of boscalid, fluopyram, solatenol, and adepidyn on A. solani isolates possessing individual SDH mutations. Additionally, field trials were conducted to determine the effects of application of these SDHI fungicides on the frequency of SDH mutations. Fluopyram, solatenol, and adepidyn had high intrinsic activity against A. solani when compared with boscalid, based on in vitro assays. The application of adepidyn and solatenol resulted in greater early blight control than the application of boscalid and fluopyram in greenhouse experiments. Molecular characterization of A. solani isolates collected from the field trials determined that the frequency of the H134R-mutation can increase in response to more recently developed SDHI fungicides. In contrast, the H278R/Y- and H133R-mutations decreased to the point of being nearly absent in these field experiments